Acknowledgements - Strugielska, Ariadna; Piątkowska, Katarzyna (Theoria et Historia Scientiarum, 2018)
The editors would like to express gratitude to the reviewers of the issue prof, dr hab. Teresa Siek-Piskozub and prof, dr hab. Aleksander Szwedek and our conference sponsors Euroexam International. We would also like to thank the following individuals for their help in proofreading: Karolina Katarzyńska, David Beynon and Daniel Karczyński.